2021
DOI: 10.1159/000520141
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective Role of Hypoxia-Inducible Factors and the Mechanism

Abstract: <b><i>Background:</i></b> The kidney requires abundant blood supply, and oxygen is transmitted by diffusion through blood vessels. Most physiological metabolism of the kidney depends on oxygen, so it is very sensitive to oxygen. An increasing pool of evidence suggests that hypoxia is involved in almost all acute and chronic kidney diseases (CKDs). Vascular damage, tubular injury, and fibrosis are the main pathologies associated during hypoxia. Hypoxia-inducible factors (HIFs) are the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 99 publications
0
4
0
Order By: Relevance
“…Erythropoiesis is an early response to hypoxic exposure that can increase blood hemoglobin levels. HIF-1α accumulated under hypoxia and stimulated the expression of target genes, such as erythropoietin (EPO) and HO-1 [ 10 ]. HO-1 is thus upregulated and involved in iron and heme metabolism, reducing ferroptosis [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Erythropoiesis is an early response to hypoxic exposure that can increase blood hemoglobin levels. HIF-1α accumulated under hypoxia and stimulated the expression of target genes, such as erythropoietin (EPO) and HO-1 [ 10 ]. HO-1 is thus upregulated and involved in iron and heme metabolism, reducing ferroptosis [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of neonatal hypoxia on body weight and the brain, heart, and lungs have been investigated [ 4 , 5 , 6 , 7 , 8 ]. The kidney is also an important organ that requires high perfusion and oxygen supply, and it is sensitive to hypoxic injury [ 9 , 10 ]. However, few studies have focused on neonatal hypoxia, which is a common clinical condition in newborns with affected kidney morphology, kidney injury, and long-term effects.…”
Section: Introductionmentioning
confidence: 99%
“…Some effects towards ROS production and glycogen retaining have been described in ischemic acute kidney injury models [ 51 ], and globally antifibrotic properties in these models [ 52 ] and in cisplatin AKI models [ 53 ]. This description contrast with genetic data and reflect maybe the difference between transient and constant activations of the pathways, or of a more pro-eminent activation of HIF-2α compared to HIF-1α [ 54 ]. Despite these promising preclinical results, the results in clinical studies are so far unconclusive regarding progression of renal disease.…”
Section: Text Of Reviewmentioning
confidence: 99%
“…The role of VEGF in renal physiology and pathology has been studied in various experimental models, yet results are controversial. While it has been suggested that the inhibition of VEFG in the adult kidney is not associated with prominent changes in the glomerular fi ltration barrier, thus limiting its signifi cance (19), contrasting data have pointed to its potential renoprotective effects under pathological conditions (20). In particular, VEGF may be important in maintaining glomerular integrity in the hypertensive setting (21), however its role in hypertension-induced kidney injury has been widely overlooked.…”
Section: U N C O R R E C T E Dmentioning
confidence: 99%